Analisis Penggunaan Sistem Informasi Akuntansi terhadap Keberhasilan Usaha Kecil Menengah yang Terdaftar di Dinas Koperasi UKM Mandailing Natal - Nurul Hijjah Harahap; Rahmat Daim Harahap (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
Accounting is an informstion system that produces a report of the stakeholders about the ekonomi activitas and coundition of the company.micro.Small medium Enterprises (MSMEs) in the indonesia at nation’s economy cantilever,a lot of these company have not been applied accounting in the their business. The objective objective of tis research is to identify and analyze the application and the obstacle of accounting at the micro,Small Medium Enterprises (MSMEs).the result showed that use of accounting informationsystem is positive and significant effect on the success of small and medium businesses registered in the enterprises of mandailing Natal Coperative Office.